The effect of Academic Supervision and Compensation on the Teaching Motivation of Teachers at MTs Nurfadhilah Manggarupi Gowa - Ainullah, Mukrim; Yuspiani, Yuspiani; Sola, Ermi (Abjadia : International Journal of Education, 2025)
This study was motivated by the importance of teacher teaching motivation in supporting the quality of learning in madrasahs. Two factors believed to play a role in increasing teacher motivation are academic supervision and compensation. Academic supervision is a guidance process carried out by a supervisor, namely the school principal, to improve the quality of teaching conducted by teachers. Effective academic supervision by the head of the madrasah can help teachers develop their competencies, while appropriate compensation serves as an external incentive that influences work enthusiasm. However, the influence of these two factors on teaching motivation still needs to be further examined, especially in the context of Madrasah Tsanawiyah Nurfadhilah Manggarupi Gowa. Madrasah Tsanawiyah is a lower secondary education level within the Islamic education system in Indonesia, equivalent to junior high school (grades 7–9) in the international education system. Based on these findings, it can be concluded that academic supervision and compensation do influence teaching motivation, although the effect is relatively weak. Therefore, it is recommended that the madrasah head provide appreciation to high-performing teachers to improve their motivation and performance. In addition, teachers are expected to remain motivated to develop their professionalism through training, especially in the preparation of learning tools, and to develop the habit of reviewing literature relevant to their areas of expertise.